Nurses’ Competencies in Providing Palliative Care for HIV/AIDS Patients in dr. Ario Wirawan Pulmonary Hospital, Salatiga - Desi Desi; Yulius Yusak Ranimpi; M. Aziz Anwar (ANIMA Indonesian Psychological Journal, 2017)
The aim of this research was to identify nurses’ competencies (cognitive, psychomotor and af-fective) in providing palliative care for HIV/AIDS patients. Using narrative qualitative approach, data were collected through both structured and non-structured interviews and also direct observations on research participants. Participants in this study were nurses (N = 5) of dr. Ario Wirawan Pulmonary Hospital. Data were coded in accordance to aspects and interview indicators. Result showed that participants did not have information about what and how palliative care should be carried out, and also about SK Menkes No. 812/MENKES/SK/VII/2007 that is targeted at all health professionals. This influenced participants to implement both psychomotor and affective competencies related to palliative care. Factors influencing participants’ lack of knowledge and competencies were personal factor, rooms’ routine, time and limited human resources. HIV/AIDS patients received general care with emphasis on collaborative medical treatments.